Getting to grippe with influenza: an investigation of why the disease is called that - Bekker-Nielsen Dunbar, Maria; Agirrezabal, Manex; Bekker-Nielsen, Tønnes (CHR 2024: Computational Humanities Research 2024, 2024)
We investigate inﬂuenza-related terminology to gain a deeper understanding of what may have driven the choice in disease name when competing options were available. It is unclear why inﬂuenza in English should be called “inﬂuenza” and not “grippe” as the latter is seemingly the most common term for inﬂuenza within Indo-European languages. We examined why inﬂuenza is referred to as “inﬂuenza” in English using minimum edit distance to determine the available space in a language for a new disease term. We included other European languages for comparison. Available space may part of but not the full reason for why diseases are called what they are called when competing options are available.